LEXICAL AND GRAMMATICAL PECULIARITIES OF EVERYDAY IDIOMS IN ENGLISH AND RUSSIAN LANGUAGES - Исмагулова, Г.К.; Мастрюкова, Н.В. (PUBLISHINGS of Kostanay State Pedagogical Institute, 2014)
In this article we focus on everyday idioms, their lexical and grammatical peculiarities and comparative analysis in Russian and English languages. Also in this work we consider idioms in general and their different classifications, there are examples of Russian and English idioms, present their comparative analysis.
Keywords: idioms; lexical and grammatical peculiarities; everyday communication; classification of idioms